2014
DOI: 10.1039/c4ta01628a
|View full text |Cite
|
Sign up to set email alerts
|

Structural, textural and acid–base properties of carbonate-containing hydroxyapatites

Abstract: HAP solids were prepared with different Ca/P ratios and Na+ cations before being characterized by XRD, XPS, LEIS, NMR, IR, and TGA. Their acid–base properties were then measured and discussed in relation to the characterization results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 42 publications
12
127
0
1
Order By: Relevance
“…8). In previous reports, a good correlation was derived between anisotropic crystallite shape obtained from XRD and grain shape observed in SEM [38]. Our results herein suggested that there might be an intrinsic relation between the Ca/P ratio and size of HAP RPB , which need further investigation in the future.…”
Section: Size-controlled Synthesis Of Hap Rpbsupporting
confidence: 79%
“…8). In previous reports, a good correlation was derived between anisotropic crystallite shape obtained from XRD and grain shape observed in SEM [38]. Our results herein suggested that there might be an intrinsic relation between the Ca/P ratio and size of HAP RPB , which need further investigation in the future.…”
Section: Size-controlled Synthesis Of Hap Rpbsupporting
confidence: 79%
“…also reported a shoulder signal at high chemical shift, around 5.4 ppm, which they attributed to surface nonprotonated phosphate groups on the basis of the dependence of this contribution on thermal treatment and on the pH of solution let in contact with the sample. 40 Such surface PO 4 3− assignment might also explain the relative higher contribution of this species in the stoichiometric compound (and also in over stoichiometric compounds, results not shown, and in ref 32) compared to the under-stoichiometric one: one may reasonably expect a higher concentration of terminal nonprotonated phosphate groups at the surface of a stoichiometric compound. Indeed, beyond the increase of the PO 4 3− /HPO 4 2− relative concentration in the bulk with increasing the Ca/P ratio [Ca 10−x (HPO 4 ) x (PO 4 ) 6−x ) (OH) 2−x ], 10 the same trend is expected to occur at the surface.…”
Section: H Mas Inversion Recoverymentioning
confidence: 89%
“…16, binding energy shift of a protonated base (B site) being larger than for an electron doublet donation (L site). Specific examples have been published for acidic zeolites and silica-aluminas [109] and basic hydroxyapatites [110], and one usually analyses Fig. 15 Relationship between m N-H vibration of pyrrole and N 1s and O 1s binding energy values for Yand X-type FAU zeolites (top and bottom lines, respectively) and scheme of the adsorption adapted from Ref.…”
Section: Xps Techniquementioning
confidence: 99%